Comparison of different small molecular weight alcohols for sustaining sulfidogenic bioreactors maintained at moderately low pH - Santos, Ana Laura; Johnson, D. Barrie (Frontiers in Bioengineering and Biotechnology, 2022)
Sulfate-reducing bacteria (SRB) catalyse the dissimilatory reduction of sulfate to hydrogen sulfide using a wide range of small molecular weight organic compounds, and hydrogen, as electron donors. Here we report the effects of different combinations of small molecular weight alcohols on the performance and bacterial composition of a moderately low pH sulfidogenic bioreactor (pH 4.0-5.5) operated at 35°C in continuous flow mode. Ethanol alone and methanol or ethanol used in combination with glycerol were evaluated based on their equivalent amounts of carbon. Although evidenced that methanol was utilised as electron donor to fuel sulfidogenesis at pH 5.5, rates of sulfate reduction/sulfide production were negatively impacted when this alcohol was first introduced to the system, though these rates increased in subsequent phases as a result of adaptation of the microbial community. Further increased dosage of methanol again caused rates of sulfidogenesis to decrease. Methanol addition resulted in perturbations of the bioreactor microbial community, and species not previously detected were present in relatively large abundance, including the sulfate-reducer Desulfovibrio desulfuricans. Ethanol utilization was evidenced by the increase in rates of sulfidogenesis as the dosage of ethanol increased, with rates being highest when the bioreactor was fed with ethanol alone. Concentrations of acetate in the effluent liquor also increased (up to 8 mM) as a result of incomplete oxidation of ethanol. This alcohol continued to be used as the electron donor for sulfate reduction when the bioreactor pH was decreased incrementally (to pH 4.0), but rates of sulfidogenesis decreased. The relative abundance of Dv. desulfuricans diminished as the bioreactor pH was lowered, while that of the acidophilic Firmicute Desulfosporosinus acididurans increased. This study has shown that all three alcohols can be used to fuel microbial sulfidogenesis in moderately acidic liquors, though the cost-effectiveness, availability and toxicity to the microbial community will dictate the choice of substrate.